Improving students’ achievement in fractions using inquiry-based instructional strategy enriched with origami activities - Tella, Adedeji; Sulaimon, Folasade Amina (Indonesian Journal of Science and Mathematics Education, 2022)
Teaching fractions in primary schools presents challenges that require innovative instructional strategies. Inquiry-based learning, when enhanced with origami activities, provides a hands-on approach to improving students' understanding of fractions. This study examines the effects of an inquiry-based instructional strategy enriched with origami activities on students' achievement in fractions and the moderating effect of gender in Oyo State, Nigeria. A quasi-experimental pretest-posttest control group design with a 2×2 factorial matrix was used. The sample comprised 55 male and 33 female students from two randomly selected public primary schools. Two intact classes were randomly assigned to the experimental and control groups. Data were collected using a students' achievement test in fractions, and teachers' instructional guides, and the data were analyzed using analysis of covariance and estimated marginal means. The findings reveal a significant main effect of the instructional strategy on students’ achievement, while gender did not have a significant effect. This suggests that the strategy is effective for diverse student groups. The study concludes that integrating origami into Inquiry-Based Learning (IBL) enhances students' fraction learning outcomes. The implications include advocating for interactive, hands-on teaching approaches in mathematics education and encouraging curriculum planners and educators to adopt engaging methodologies that foster deeper conceptual understanding.